The Role of Islamic Education in Enhancing Social Integration of the Ummah: A Theoretical Review - M. Rozi Azhari (Indonesian Journal of Education and Science, 2025)
Islamic education played a strategic role in fostering social integration among diverse communities in Indonesia. This study aimed to theoretically examine the role of Islamic education in enhancing social integration, identify relevant Islamic values, and formulate a conceptual model of Islamic education that supported social harmony. Using a qualitative approach based on a literature review, this research analyzed concepts of Islamic education and social integration through primary and secondary sources. The findings revealed that Islamic education played a crucial role in internalizing the values of ukhuwah Islamiyyah (brotherhood), tasāmuh (tolerance), ʿadālah (justice), syura (consultation), as well as ihsan and sadaqah (social responsibility). These values contributed to social harmony through their integration into formal education curricula, community-based programs, and cultural approaches. The proposed conceptual model emphasized the synergy between formal, non-formal, and cultural education to foster sustainable social solidarity. This study contributed theoretically to the literature on Islamic education and offered practical guidance for policymakers, educators, and educational institutions.